2004
DOI: 10.1007/s00109-004-0543-2
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian cell transduction and internalization properties of λ phages displaying the full-length adenoviral penton base or its central domain

Abstract: In recent years a strong effort has been devoted to the search for new, safe and efficient gene therapy vectors. Phage lambda is a promising backbone for the development of new vectors: its genome can host large inserts, DNA is protected from degradation by the capsid and the ligand-exposed D and V proteins can be extensively modified. Current phage-based vectors are inefficient and/or receptor-independent transducers. To produce new, receptor-selective and transduction-efficient vectors for mammalian cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Most attempts to enhance lambda phage-mediated gene transfer to mammalian cells have concentrated on optimizing the binding of phage particles to mammalian cells (7,8,13,14). However, the eukaryotic cell poses numerous barriers to phage-mediated gene transfer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most attempts to enhance lambda phage-mediated gene transfer to mammalian cells have concentrated on optimizing the binding of phage particles to mammalian cells (7,8,13,14). However, the eukaryotic cell poses numerous barriers to phage-mediated gene transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the ultimate success of phage-mediated gene transfer depends on the ability to overcome multiple intracellular barriers. This is likely to require the use of combination strategies that increase the efficiency of each step involved in phage-mediated gene transfer, including cell attachment, cytoplasmic entry, endosomal escape, uncoating and nuclear import (7,15,16). …”
Section: Introductionmentioning
confidence: 99%
“…This technology was developed and explored for the most part with filamentous phage and it has been shown that surface expression of receptor-binding peptides or proteins can result in phage binding to mammalian cells and, in some cases, in phage internalization (1416,2325,35,36,52,53). When such phage contain mammalian expression cassettes, this can result in expression of encoded genes within the target cells of interest (14,15,2325,35,37). These advances have led to the proposed use of bacteriophage as gene delivery vehicles.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriophage λ has been shown to be able to accommodate the display of foreign peptides and proteins on the gpD major coat protein (3,4,15,20,28,35,38). However, in the course of our studies, we have encountered certain proteins that are poorly tolerated when displayed on the bacteriophage λ capsid at high copy number (405–420 copies per capsid), resulting in an inability to generate recombinant phage particles that display the desired molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Dickerson et al (2005) reported that engineered filamentous bacteriophage displaying cocainesequestering antibodies delivered into the central nervous system are capable of treating cocaine addiction. Receptortargeted phage might have important implications for the use of phage as a DNA vaccine or therapeutic gene delivery vehicle directed to specific cell types (Barry et al 1996;Dunn 1996;Larocca et al 1998Larocca et al , 1999Piersanti et al 2004). …”
Section: Phages For Vaccine Deliverymentioning
confidence: 99%